1997
DOI: 10.1016/s0194-5998(97)70294-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the biocompatibility of three absorbable hemostatic agents in the rat middle ear

Abstract: Absorbable gelatin sponge (Gelfoam) has been used for many years in middle ear surgery. Although the sponge is generally well tolerated, fibrosis occasionally forms in the mesotympanum; some studies indicated that the absorbable gelatin sponge may be responsible. Many of these studies lack statistical analysis. We prospectively studied three absorbable hemostatic agents in the middle ear of adult male Sprague-Dawley rats to determine which promotes fibrosis to the greatest degree: absorbable gelatin sponge (Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
1
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 13 publications
2
33
1
1
Order By: Relevance
“…Several trials have suggested that Gelfoam are biocompatible [11] and, in addition, Gelfoam packing has been long used in surgery of chronic otitis media without any complications. Some human studies suggest that absorbable gelatin film may predispose toward the formation of granulation tissue [16,17], whereas others suggest the opposite [17,18]. The present study showed no difference of granulation tissue between Gelfoam packing and no packing.…”
Section: Discussioncontrasting
confidence: 54%
“…Several trials have suggested that Gelfoam are biocompatible [11] and, in addition, Gelfoam packing has been long used in surgery of chronic otitis media without any complications. Some human studies suggest that absorbable gelatin film may predispose toward the formation of granulation tissue [16,17], whereas others suggest the opposite [17,18]. The present study showed no difference of granulation tissue between Gelfoam packing and no packing.…”
Section: Discussioncontrasting
confidence: 54%
“…Gelfoam® has a long history of use as a hemostatic agent [24]. Gelfoam® has also been tested in bone repair [25, 26].…”
Section: Discussionmentioning
confidence: 99%
“…Gelfoam, a highly porous, gelatin sponge derived from porcine skin, is a material potentially suitable as a delivery vehicle for MSCs in cartilage regeneration therapy. It has a long history of use as a hemostatic agent 30 and also has been tested in bone repair, 31 both alone 32 and in conjunction with cytokines. 33,34 Gelfoam also has been shown to be supportive of chondrogenic matrix production in vitro when seeded with bovine chondrocytes.…”
Section: Introductionmentioning
confidence: 99%